Experimental and numerical investigation of compressive behavior of lattice structures manufactured through projection micro stereolithography - Dar, U.A. (Elsevier Ltd, 2020)
The present work focuses on investigating the effect of lattice geometry on compression behavior, deformation mechanism and energy absorption capability of 3D printed polymeric micro-lattice structures. The mechanical characteristics of lattice cores comprising of periodic body centered cubic (BCC) architecture unit-cells, printed with projection micro-stereolithography (PÎ¼SL) based 3D printing technique were experimentally and numerically examined. For a fixed mass and corresponding relative density of lattice, five variants of BCC lattice structures were built by varying unit cell size, numbers and its strut diameter. The quasi-static compression tests were performed to determine the load-displacement history, stress-strain curves and deformation modes of lattice structures. The experimental results show that number of unit cells with in a certain volume of lattice block can have significant effect on compression properties of lattice structure. Within the same geometric envelop and mass properties, the lattice containing higher number of cells with reduced strut diameter tends absorb more energy as compared to a lattice with fewer number of cells with increased strut diameter. The elastic modulus, collapse and plateau stresses of lattice increase while densification strain decreases with the increase in number of unit cells. Moreover, there exists a certain number of cells in certain volume of lattice structure for which the energy absorption is higher, after that number the effect not significant. The deformation behavior of lattice was inspected and bending dominant deformation modes were observed in all lattice structures. The lattice with small cells shows progressive layer by layer collapse while for larger cell sized lattice show signs of buckling effect with central localized deformation modes. Lastly, the experimental outcomes were numerically implemented in finite element (FE) solver LS-DYNA to model the compression process, collapse behavior and deformation modes of lattice blocks. The compression characteristics and collapse modes predicted by FE model were in good agreement with experimental findings. Â© 2020 Elsevier Ltd